Eksperimen Permainan Memancing Ikan Warna Terhadap Kemampuan Mengenal Warna Pada Anak Usia 4-5 Tahun - Puspita, Galuh Dhyah; Khotimah, Nurul (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2023)
Children aged 4-5 years, kindergarten education is an option to help the child's growth and development process. One of the developments of children aged 4-5 years that needs attention is the development of their sense of sight. Through color recognition, the sensitivity of his sense of sight is honed. In addition, color recognition is an early anticipation of the occurrence of color blindness in children. This study aims to determine the influence of color fish in fishing game as one of the process to improve the cognitive ability of children aged 4-5 years in recognizing colors. The type of research used is quantitative research through the One Group Pre-Test Post-Test Design method. The data collection techniques used are observation and assessment the final result. Observation results from the pre-test and post-test were then calculated using the Wilcoxon Signed Rank test. The result of this study that there is an influence on color fish fishing game on the ability to recognize colors in children aged 4-5 years in Dharma Wanita Persatuan Lampah Kindergarten. Through the Wilcoxon test, it is known that the signification value is 0.000 < 0.05. The post-test showed that 89% of children were in the starting to develop (MB) category and 11% were developing as expected (BSH). Meanwhile, the post-test results show that 100% of children increased into the very well developed category (BSB). Thus, it can be concluded that the color fish of fishing game can be used to improve the ability to recognize colors in children aged 4-5 years in Dharma Wanita Persatuan Lampah Kindergarten, Gresik.